"Not for Human Consumption": A Descriptive Investigation into User Characteristics, Motives, and Consequences Associated with Bath Salt Use. Issue 3 (27th May 2019) - Zimmerman, Lauren; Kilwein, Tess M.; Beyer, Danielle; Marks, Cassidy; Looby, Alison
ABSTRACT: Synthetic cathinones, commonly referred to as "bath salts, " are recreational designer drugs that recently emerged as a drug of abuse. However, little is known about bath salt users, particularly in the United States (US). This descriptive study aims to better characterize users and user behavior, including common motives for and consequences of use. Individuals with a lifetime history of bath salt use (BSU; n = 110) completed an Internet survey. Participants (50.9% male) were aged 18 to 58 ( M = 31.21, SD  = 10.25) years and were from 32 US states. Most participants reported past-year BSU, via intranasal use, obtained from a friend or acquaintance. Recreational motives (e.g., to get high, experimentation) were commonly reported, as was use due to drug availability. Participants reported experiencing an average of 5.50 consequences, with both physical (e.g., rapid heartbeat) and psychological (e.g., anxiety) negative outcomes commonly reported. This descriptive information on BSU from a small but diverse sample of users may inform efforts to reduce use and negative consequences, such as eliminating riskier routes of administration (e.g., injection) and targeting specific motives for use (e.g., providing alternative methods for mood expansion).